2015
DOI: 10.1073/pnas.1500913112
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual transparency from image deformation

Abstract: Human vision has a remarkable ability to perceive two layers at the same retinal locations, a transparent layer in front of a background surface. Critical image cues to perceptual transparency, studied extensively in the past, are changes in luminance or color that could be caused by light absorptions and reflections by the front layer, but such image changes may not be clearly visible when the front layer consists of a pure transparent material such as water. Our daily experiences with transparent materials o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 37 publications
6
52
0
Order By: Relevance
“…This speculation is supported by the observation that, again unlike the fixed-phase patterns, the subjective naturalness in the random modulations monotonically increased as the blur increased (Fig. 5), and is consistent with the notion that the visual system has heuristic mechanisms for material perception using simple visual features correlated with the physical material profiles in nature (Fleming, 2014; Kawabe et al, 2015; Kawabe, Maruya, and Nishida, 2015; Marlow, Kim, and Anderson, 2012; Motoyoshi et al, 2007; Norman et al, 2007). …”
Section: Discussionsupporting
confidence: 77%
“…This speculation is supported by the observation that, again unlike the fixed-phase patterns, the subjective naturalness in the random modulations monotonically increased as the blur increased (Fig. 5), and is consistent with the notion that the visual system has heuristic mechanisms for material perception using simple visual features correlated with the physical material profiles in nature (Fleming, 2014; Kawabe et al, 2015; Kawabe, Maruya, and Nishida, 2015; Marlow, Kim, and Anderson, 2012; Motoyoshi et al, 2007; Norman et al, 2007). …”
Section: Discussionsupporting
confidence: 77%
“…Another line of vision science that influenced the development of Deformation Lamps is the research on material perception. Our recent study showed that dynamic deformation is a useful visual cue for human observers to see liquid‐like materials . As it had been shown that projection mapping was able to change the optical material properties of real objects, we attempted to change the mechanical material properties.…”
Section: Human Visual Processingmentioning
confidence: 99%
“…Our recent study showed that dynamic deformation is a useful visual cue for human observers to see liquid-like materials. 16,17 As it had been shown that projection mapping was able to change the optical material properties of real objects, we attempted to change the mechanical material properties. This was our initial motivation for developing Deformation Lamps.…”
Section: Materials From Motion Flowmentioning
confidence: 99%
“…The image deformation due to refraction is a strong cue of the presence of transparent materials for computer vision [48]. For human vision, the impression of transparent liquid is generated solely by dynamic image deformation, and the deformation pattern could be a random modulation of a specific range of spatiotemporal frequencies [24].…”
Section: Picture Deformation By Camera-projection Systemmentioning
confidence: 99%